Conformational Change of Amyloid-β 40 in Association with Binding to GM1-Glycan Cluster - Yuhei Tachi (Nature Portfolio, 2019)
Abstract Aggregates of amyloid-β (Aβ) peptide are well known to be the causative substance of Alzheimer’s disease (AD). Recent studies showed that monosialotetrahexosylganglioside (GM1) clusters induce the pathological aggregation of Aβ peptide responsible for the onset and development of AD. However, the effect of GM1-glycan cluster on Aβ conformations has yet to be clarified. Interactions between Aβ peptide and GM1-glycan cluster is important for the earliest stage of the toxic aggregation on GM1 cluster. Here, we performed all-atom molecular dynamics (MD) simulations of Aβ40 on a recently developed artificial GM1-glycan cluster. The artificial GM1-glycan cluster facilitates the characterization of interactions between Aβ40 and multiple GM1-glycans. We succeeded in observing the binding of Aβ40 to the GM1-glycan cluster in all of our MD simulations. Results obtained from these MD simulations indicate the importance of HHQ (13-15) segment of Aβ40 for the GM1-glycan cluster recognition. This result is consistent with previous experimental studies regarding the glycan recognition of Aβ peptide. The recognition mechanism of HHQ (13-15) segment is mainly explained by non-specific stacking interactions between side-chains of histidine and rings of sugar residues, in which the HHQ regime forms coil and bend structures. Moreover, we found that Aβ40 exhibits helix structures at C-terminal side on the GM1-glycan cluster. The helix formation is the initial stage of the pathological aggregation at ceramide moieties of GM1 cluster. The binding of Lys28 to Neu triggers the helix formation at C-terminus side because the formation of a salt bridge between Lys28 and Neu leads to change of intrachain interactions of Aβ40. Our findings suggest that the pathological helix formation of Aβ40 is initiated at GM1-glycan moieties rather than lipid ceramide moieties.